Statistische Kenngrössen der prosodischen Wort- und Silbenstruktur in der litauischen Standardsprache - Karosienė, Vida; Girdenis, Aleksas (Baltistica, 2000)
The statistical structure of words and syllables in standard Lithuanian A statistical analysis carried out by computer (programming language PL/1) shows that in the texts of Standard Lithuanian the vast majority of words are composed of two, three and four phonological syllables (the average length of the words being 2.9 syllables). All longer words belong to the periphery of the system. Stressed monosyllabic words are rare. In most of the polysyllabic words the stress falls on the penultimate syllable (paroxytonic stress), but in very long words it usually falls on the third last syllable. In the texts analysed, long (heavy, two mora) syllables are more common than short (light, monomora) ones. Long circumflex syllables occur approximately 1.4 more frequently than acute ones. Two relatively autonomous prosodic subsystems can be distinguished: word ending and word stem. These subsystems considerably differ in respect of the ratio of stressed and unstressed long and short vowels. In word-final syllables stressed short and unstressed long vowels in the stem of a word are more common than long acute vowels. The obtained statistical results can be used in both synchronic and diachronic linguistic research; perhaps they can account for certain tendencies in the development of dialectal accentuation and vowel quantity.